Lenvatinib combined with anti-PD-1 antibodies plus transcatheter arterial chemoembolization for neoadjuvant treatment of resectable hepatocellular carcinoma with high risk of recurrence: A multicenter retrospective study - Wu, Jun-Yi; Wu, Jia-Yi; Li, Yi-Nan; Qiu, Fu-Nan; Zhou, Song-Qiang; Yin, Zhen-Yu; Chen, Yu-Feng; Li, Bin; Zhou, Jian-Yin; Yan, Mao-Lin (Frontiers in Oncology, 2022)
Background: Early recurrence is common after surgical resection (SR) for hepatocellular carcinoma (HCC) with high risk of recurrence and is associated with poor prognosis. The combinations of lenvatinib (LEN), anti-PD-1 antibodies (PD-1) and transcatheter arterial chemoembolization (TACE) (triple therapy) has shown better trend in tumor response and survival outcomes on unresectable HCC. It is unknown whether triple therapy for neoadjuvant treatment of resectable HCC with high risk of recurrence is effective. This article aimed to compare the outcomes of surgery alone and neoadjuvant combination treatment with triple therapy before SR in patients with HCC with high risk of recurrence. Methods: A retrospective study was conducted on patients diagnosed with HCC with high risk of recurrence who received treatment with or without triple therapy. The records of 24 patients in the triple therapy group and 76 patients in the surgery-alone group were analyzed. Propensity score matching (PSM) was performed to minimize the influence of potential confounders. Results: One hundred patients were enrolled. In the triple therapy group, 8 (33.3%) and 12 (50.0%) patients had complete and partial responses, respectively, as assessed by an investigator. Before PSM, the overall survival (OS) rates for the triple therapy group at 6, 12, 18, and 24 months were 100.0%, 100.0%, 100.0%, and 85.7%, respectively, compared with corresponding 92.1%, 73.7%, 53.9%, and 48.7% for the surgery-alone group (P<0.001). The disease-free survival (DFS) rates were 82.2%, 66.95%, 48.8%, and 48.8% for the triple therapy and 41.92%, 28.34%, 27.05%, and 22.99% for the surgery-alone group (P=0.003). After PSM, DFS and OS were significantly longer in the triple therapy group than in the surgery-alone group (DFS, p=0.019; OS, p=0.003). Conclusions: Neoadjuvant combination treatment before SR had a high rate of tumor response and provided significantly better postoperative survival outcomes than surgery alone in patients with HCC with high risk of recurrence.